Resonant interaction between laser and electrons undergoing betatron oscillations in the bubble regime. (October 2015) - Curcio, Alessandro; Giulietti, Danilo; Dattoli, Giuseppe; Ferrario, Massimo
Abstract : The betatron radiation in the bubble regime is studied in the presence of resonant interaction between the accelerated electrons and the driver laser pulse tail. The calculations refer to experimental parameters available at the FLAME laser facility at the National Laboratories of Frascati (LNF), and represent the radiation spectra and spatial distributions to be expected in forthcoming experiments.